Plains Zebras Prioritize Foraging Without Sacrificing Social Bonds During a Severe Drought - Severine B. S. W. Hex; Erin S. Isbilen; Daniel I. Rubenstein (Ecology and Evolution)
ABSTRACT Anthropogenically induced climate change has significantly increased the frequency of acute weather events, such as drought. As human activities amplify environmental stresses, animals may be forced to prioritize survival over behaviors less crucial to immediate fitness, such as socializing. Yet, social bonds may also enable individuals to weather the deleterious effects of environmental conditions. We investigated how the highly social plains zebra (Equus quagga) modify their activity budgets, social networks, and multimodal communication during a drought. Although animals prioritized feeding and the number of social interactions dramatically decreased in the late drought period, social associations remained robust. We observed age/sex class‐specific changes in social behavior, reflecting the nutritional needs and social niche of each individual. Stallions devoted more time to greeting behaviors, which could mitigate harassment by bachelor males and facilitate grazing time for the females of the harem. Juveniles significantly increased time spent active socializing, despite mothers showing the greatest decrease in the number of social interactions. Instead, unrelated, nonlactating females served as social partners, accommodating both juveniles' social needs and lactating mothers' nutritive requirements. Using a network‐based representation of multimodal communication, we observed a decrease in the number of signals used during the drought. Individuals used less diverse multimodal combinations, particularly in the costly context of aggression. These findings illustrate how social roles and differential responses to acute environmental stress within stable social groups may contribute to species resilience, and how communication flexibly responds to facilitate both survival and sociality under harsh environmental conditions.